Analysis of The Difficulties of Teachers at the Darunnajah Islamic Boarding School in Jakarta to Carry Out Classroom Action Research (PTK) - Rika Handayani; Muchammad Ibnu Muzakir; Ita Handayani (At-Tathbīq: Journal of Education and Learning, 2025)
This research analyzes the difficulties experienced by teachers at the Darunnajah Islamic Boarding School, Jakarta, in carrying out Classroom Action Research (PTK). The quality of teacher professionalism is key to ensuring students receive the best education, and PTK is an important tool to improve the learning process. However, implementing PTK in the field is often not easy, and many teachers face various challenges, including in the Islamic boarding school environment. This research aims to identify teachers' understanding of PTK, the difficulties they face, and solutions to overcome them. A qualitative approach with case study methods is used to understand this phenomenon in depth. Primary data was collected through interviews with teachers at the Darunnajah Islamic Boarding School, while secondary data was obtained from relevant school records, books and journals. Data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions.The research results show that teachers have a basic understanding of PTK as a practical tool for improving learning, but their knowledge of formal methodology is still minimal. The main difficulties found were limited time, minimal understanding of research methodology, lack of writing culture, and lack of systemic support from the school. The proposed solution is to organize practice-based training, build a research and writing culture, and provide systematic support through school policies, incentives, and collaboration with external parties.